Extracellular vesicles from human cardiovascular progenitors trigger a reparative immune response in infarcted hearts. Issue 1 (12th February 2020) - Lima Correa, Bruna; El Harane, Nadia; Gomez, Ingrid; Rachid Hocine, Hocine; Vilar, José; Desgres, Manon; Bellamy, Valérie; Keirththana, Kamaleswaran; Guillas, Chloé; Perotto, Maria; Pidial, Laetitia; Alayrac, Paul; et al.
Abstract: Aims: The cardioprotective effects of human induced pluripotent stem cell-derived cardiovascular progenitor cells (CPC) are largely mediated by the paracrine release of extracellular vesicles (EV). We aimed to assess the immunological behaviour of EV-CPC, which is a prerequisite for their clinical translation. Methods and results: Flow cytometry demonstrated that EV-CPC expressed very low levels of immune relevant molecules including HLA Class I, CD80, CD274 (PD-L1), and CD275 (ICOS-L); and moderate levels of ligands of the natural killer (NK) cell activating receptor, NKG2D. In mixed lymphocyte reactions, EV-CPC neither induced nor modulated adaptive allogeneic T cell immune responses. They also failed to induce NK cell degranulation, even at high concentrations. These in vitro effects were confirmed in vivo as repeated injections of EV-CPC did not stimulate production of immunoglobulins or affect the interferon (IFN)-γ responses from primed splenocytes. In a mouse model of chronic heart failure, intra-myocardial injections of EV-CPC, 3 weeks after myocardial infarction, decreased both the number of cardiac pro-inflammatory Ly6Chigh monocytes and circulating levels of pro-inflammatory cytokines (IL-1α, TNF-α, and IFN-γ). In a model of acute infarction, direct cardiac injection of EV-CPC 2 days after infarction reduced pro-inflammatory macrophages, Ly6Chigh monocytes, and neutrophils in heart tissue as compared to controls. EV-CPC also reduced levels of pro-inflammatory cytokines IL-1α, IL-2, and IL-6, and increased levels of the anti-inflammatory cytokine IL-10. These effects on human macrophages and monocytes were reproduced in vitro ; EV-CPC reduced the number of pro-inflammatory monocytes and M1 macrophages, while increasing the number of anti-inflammatory M2 macrophages. Conclusions: EV-CPC do not trigger an immune response either in in vitro human allogeneic models or in immunocompetent animal models. The capacity for orienting the response of monocyte/macrophages towards resolution of inflammation strengthens the clinical attractiveness of EV-CPC as an acellular therapy for cardiac repair. Graphical Abstract: